2013
DOI: 10.1111/ele.12197
|View full text |Cite
|
Sign up to set email alerts
|

What explains variation in the impacts of exotic plant invasions on the nitrogen cycle? A meta‐analysis

Abstract: Exotic plant invasions can notably alter the nitrogen (N) cycle of ecosystems. However, there is large variation in the magnitude and direction of their impact that remains unexplained. We present a structured meta-analysis of 100 papers, covering 113 invasive plant species with 345 cases of invasion across the globe and reporting impacts on N cycle-related metrics. We aim to explain heterogeneity of impacts by considering methodological aspects, properties of the invaded site and phylogenetic and functional c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

16
210
3
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(235 citation statements)
references
References 82 publications
(171 reference statements)
16
210
3
6
Order By: Relevance
“…plants change the abundance, diversity, and structure of plant and animal communities (Hejda et al 2009;Lenda et al 2013), and often considerably modify physicochemical and biological properties of the soil environment, thereby potentially affecting key ecosystem processes (Vilà et al 2011;Castro-Díez et al 2014;Majewska et al 2015;Stefanowicz et al 2016;Zubek et al 2016;Broadbent et al 2017;CastroDíez and Alonso 2017;Lavoie 2017;Rodríguez-Caballero et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…plants change the abundance, diversity, and structure of plant and animal communities (Hejda et al 2009;Lenda et al 2013), and often considerably modify physicochemical and biological properties of the soil environment, thereby potentially affecting key ecosystem processes (Vilà et al 2011;Castro-Díez et al 2014;Majewska et al 2015;Stefanowicz et al 2016;Zubek et al 2016;Broadbent et al 2017;CastroDíez and Alonso 2017;Lavoie 2017;Rodríguez-Caballero et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Studies based on meta-analysis indicated that plant invasions generally increase nutrient (C, N, P) pools and also enhance the rate of soil processes such as litter decomposition and mineralization, possibly accelerating nutrient cycling (Liao et al 2008;Vilà et al 2011;Castro-Díez et al 2014). This is because invasive species have significantly higher, in comparison to non-invasive ones, values of performancerelated traits such as physiology, leaf-area allocation, shoot allocation, growth rate, size and fitness, which are driving factors in regulating C and N cycles (Liao et al 2008;Van Kleunen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitude and direction of changes in soil characteristics and processes brought about by invasion depend on local habitat conditions, invasive plant species traits, and/or the interaction of both (Meyerson et al 2000;Ehrenfeld 2003;Koutika et al 2007;Dassonville et al 2008;Scharfy et al 2009;Vilà et al 2011;Hulme et al 2013;Castro-Díez et al 2014). Dassonville et al (2008) reported that invasion increased nutrient concentrations of surface soils with initially low nutrient concentrations, while under the opposite conditions, a negative impact was mainly observed.…”
Section: Introductionmentioning
confidence: 99%
“…Modifying effects of invasive woody species on habitat was also reported from several biomes across the world (e.g., Vitousek 1990; Ehrenfeld 2003;Stohlgren and Rejmánek 2014;Castro-Díez et al 2014;Menge and Chazdon 2016). Among woody species, some guilds are especially responsible for ecosystem change, e.g., nitrogenfixing species (e.g., Ehrenfeld 2003; Rice et al 2004;Castro-Díez et al 2014;Jo et al 2015) or coniferous trees planted on sites typical to broadleaved trees (e.g., Binkley and Valentine 1991;Augusto et al 2002;Zerbe and Wirth 2006;Jagodziński et al 2015).…”
Section: Introductionmentioning
confidence: 84%
“…Tree species (both alien and native) influence light availability (Knight et al 2008;Niinemets 2010), mineral nutrient cycling (Augusto et al 2002;Reich et al 2005;Dauer et al 2007;Mueller et al 2012), soil acidity (Binkley and Valentine 1991;Binkley and Giardina 1998;Mueller et al 2012), decomposition rate (Hobbie et al 2006(Hobbie et al , 2010, fine root and leaf lifespans (Withington et al 2006), ectomycorrhizal infections (Dickie et al 2006;Trocha et al 2012), and soil biota (Mueller et al 2015(Mueller et al , 2016. Modifying effects of invasive woody species on habitat was also reported from several biomes across the world (e.g., Vitousek 1990; Ehrenfeld 2003;Stohlgren and Rejmánek 2014;Castro-Díez et al 2014;Menge and Chazdon 2016). Among woody species, some guilds are especially responsible for ecosystem change, e.g., nitrogenfixing species (e.g., Ehrenfeld 2003; Rice et al 2004;Castro-Díez et al 2014;Jo et al 2015) or coniferous trees planted on sites typical to broadleaved trees (e.g., Binkley and Valentine 1991;Augusto et al 2002;Zerbe and Wirth 2006;Jagodziński et al 2015).…”
Section: Introductionmentioning
confidence: 92%